Pajak Bumi dan Bangunan serta Relevansinya dengan Konsep Al-Kharaj Abu Yusuf - Lamondo, Lamondo (IAIN Kendari, 2022)
This research is based on a critical study of the economic thought of Abu Yusuf Ulama, famous for his monumental work, Kitab al-Kharaj. This research aims to find out the relevance of Land and Building Tax (PBB) in Indonesia to the concept of tax during the Abu Yusuf period. This research uses qualitative methods through a literature review (Library Research). The results of this study explain that PBB and the concept of al-Kharaj Abu Yusuf have relevance in the context of land tax. However, there needs to be more relevant in the building tax sector.